Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan (Studi Pada Nasabah Asuransi Unit Link PT. Prudential Life Assurance Semarang) - Yurianto, Andre Octo; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2021)
Abstract: One of the most widely recognized insurance brands recognized by the Indonesian people as Unit Link's pioneer is PT. Prudential Life Assurance. Based on data on growth in the number of customers, from 2015 to 2019, Prudential in Semarang experienced a fluctuating number of policyholders. Therefore, service quality and product quality can be assumed to be the factors causing these fluctuations. This study aims to determine the effect of service quality and product quality on customer satisfaction at PT. Prudential Life Assurance Semarang. The sample used was 304 respondents from customers of PT. Prudential Life Assurance Semarang. This study uses the SPSS version 26 and uses quantitative analysis with validity, reliability, correlation coefficient, determination coefficient, simple and multiple regression, significance t-test and F test. This study indicates that service quality and product quality partially influence customer satisfaction, and simultaneously there is a significant influence between service quality and product quality on customer satisfaction. Based on the results of the research, the authors suggest to provide and expand the service place. Provide education and guide customers when accessing the Prudential application, increasing training for agents to better product mastery. Besides, evaluating premium prices by making product specifications according to customer needs and capabilities, and insurance products are not combined with investments with various protection benefits.Keywords: Service Quality; Product Quality and Customer Satisfaction,Abstraksi: Salah satu asuransi yang memiliki brand yang dikenal luas oleh masyarakat Indonesia sebagai pelopor Unit Link adalah PT. Prudential Life Assurance. Berdasarkan data pertumbuhan jumlah nasabah, tahun 2015 sampai tahun 2019 Prudential di Semarang mengalami jumlah pemegang polis yang fluktuatif. Maka dari itu, kualitas pelayanan dan kualitas produk dapat diduga menjadi faktor penyebab fluktuasi tersebut. Penelitian ini bertujuan untuk mengetahui pengaruh kualitas pelayanan dan kualitas produk terhadap kepuasan nasabah PT. Prudential Life Assurance Semarang. Penelitian ini menggunakan SPSS versi 26. Hasil penelitian ini menunjukkan bahwa kualitas pelayanan dan kualitas produk berpengaruh secara parsial terhadap kepuasan pelanggan dan secara simultan terdapat pengaruh signifikan antara kualitas pelayanan dan kualitas produk terhadap kepuasan pelanggan. Berdasarkan hasil penelitian penulis menyarankan untuk menyediakan dan memperluas tempat pelayanan. memberikan edukasi dan membimbing nasabah ketika mengakses aplikasi Prudential, memperbanyak pelatihan kepada agen agar penguasaan produk semakin baik. Selain itu, mengevaluasi harga premi dengan membuat produk spesifikasi sesuai dengan kebutuhan dan kemampuan nasabah, dan produk asuransi tidak dikombinasikan antara investasi dengan berbagai manfaat proteksi.Kata Kunci: Kualitas Pelayanan; Kualitas Produk dan Kepuasan Pelanggan